Studi Kasus Pengaruh Terapi Latihan Terhadap Pengurangan Jarak Intra Recti Pada Kondisi Diastasis Recti - Sari Tri Yulianti; Ayu Permata; Aulia Indah Marianda (LPPM Universitas Abdurrab, 2021)
ABSTRACT Background: Diastasis recti is an impairment characterized by the rectus abdominis muscle separates in midline at linea alba. The separation of the linea alba in diastasis recti results in the forming of a space referred to as an inter-recti distance. Symptoms in diastasis recti are an increase in the distance between the anterior borders of the rectus muscle influence the strength of the abdominal wall musculature. Various intervention techniques have been carried out to reduce the intra-recti distance in diastatic recti conditions, but research is still limited on the effect of exercise therapy on reducing the intra-recti distance in diastasis recti. The purpose of the study was to determine the effect of exercise therapy in reducing inter-recti distance in postpartum with diastasis recti. Methods: Single case study with pre and post test design in 38 years old woman with diastasis recti. The exercise therapy protocol was carried out for 30 minutes, three times a week for four weeks. Exercise therapy consisted of abdominal exercise and pelvic floor exercise. The measurements used in this study used calipers to evaluate the reduction inter-recti distance. Results: After being given an exercise therapy intervention for four weeks, the results of the intra-recti distance reduction were obtained. The results of the initial measurement pre exercise therapy obtained E0= 3.9 cm, and at the post exercise therapy E4 = 2.4 cm. Conclusion: The results of this study indicate that exercise therapy can reduce the intra-recti distance in postpartum with diastasis recti Keywords: Diastasis recti, rectal distance, exercise therapy, calipers